Vs30 Mapping and Soil Classification in The Southern Part of Kulon Progo Using Rayleigh Wave Ellipticity Inversion - Bambang Sunardi (Jurnal Geospasial Indonesia, 2019)
Shear wave velocity from the ground surface to a depth of 30 meters (Vs30) is a parameter to determine dynamic characteristics of the soil, which can be used to assess the level of seismic hazard. Thus, Vs30 mapping has an important role in seismic hazard mitigation efforts. Vs30 can be determined by Multichannel Analysis of Surface Waves (MASW) and Spatial Autocorrelation (SPAC) methods. A simpler alternative can be done by using Rayleigh wave ellipticity. The main objective of this research is to map Vs30 in the southern part of Kulon Progo using Rayleigh wave ellipticity inversion. In this study, Rayleigh wave ellipticity inversion was performed on 42 microtremor single measurement data, scattered in the southern part of Kulon Progo. The inversion results are used to estimate the value of Vs30 and classify the soil type at the measurement points, referring to SNI 1726:2012. A Vs30 distribution map and soil type classification are obtained by applying the geostatistical interpolation method. The mapping result showed that most of the southern part of Kulon Progo has a relatively low Vs30 value. These values are in the range of 180-342 m/s, which categorized as stiff soil (SD). In this region, some parts located in the hilly and transition zones have relatively high shear wave velocities in the range of 357-578 m/s and included in the category of very dense soil/ soft rock (SC) types